Isobavachalcone reveals novel characteristics of methuosis-like cell death in leukemia cells. (1st May 2019) - Yang, Li; Song, Lili; Zhao, Shan; Ma, Chunmin; Wu, Depei; Wu, Ying-Li
Abstract: Non-apoptotic cell-death induction is a potential strategy for cancer treatment. Cytoplasmic vacuolation-associated cell death represents a novel type of non-apoptotic cell-death. Here, we showed that isobavachalcone (IBC), a naturally occurring chalcone compound, selectively induced cell death with massive cytoplasmic vacuolation in some leukemic cells but not in normal peripheral blood cells. Although the IBC-induced cell death displayed certain apoptotic changes, the caspase inhibitor Z-VAD-FMK did not significantly suppress IBC-induced cell death. IBC-induced vacuoles are acidic in nature, as revealed by neutral red staining. However, these vacuoles could not be labeled by lysosome or mitochondrial trackers. Moreover, the knockdown of several autophagy-related genes, such as LC3, Beclin-1, and ATG7, did not inhibit IBC-induced vacuolation. Transmission electron microscope examination revealed that these vacuoles mainly derived from the endosome. Surprisingly, Vacuolar-type H + -ATPase inhibitors, weak bases, such as chloroquine and AKT inhibitors, markedly abrogated vacuolization but enhance IBC-induced cell death, suggesting that IBC-induced vacuolation and cell death go into different direction and the vacuolization is a protective action rather than a part of the death mechanism. In conclusion, by using IBC as a chemical probe, we provide new characteristics of methuosis-like cell death. Inducing methuosis-like cell death may represent a novel strategy to combat leukemia. Highlights: IBC selectively induces a methuosis-like cell death in some leukemia cells. The activation of the V-ATPase and AKT are two novel properties of methuosis. Inhibition of IBC-induced cytoplasmic vacuolation enhances cell death. IBC is a promising candidate for leukemia therapy.